Implementasi Kebijakan Hygiene Sanitasi Pengelolaan Makanan dan Minuman pada Fasilitas Umum di Kota Palangka Raya - Muhaimin Noor; Dwi Rochani Fatmiasih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to provide an image of how to implement Regional Regulation No. 06 of 2008 concerning Hygiene Sanitation for the Management of Food, Beverages and Public Places in the City of Palangka Raya. The type of research used is qualitative research methods. The data source in this study consisted of primary and secondary data. The primary data source is Palangka Raya City Health Office and Palangka Raya City Health Center, TPM and TTU Owner or Person in Charge and Palangka Raya City Community while the secondary source data is Regional Regulation Number 06 the Year 2008. Techniques for collecting data through Observation, Interview and Documentation. Data analysis uses qualitative data analysis procedures, namely data reduction, data presentation, and conclusion drawing. Based on the results of the study, it can be explained that the Implementation of Regional Regulations on Hygiene Sanitation in the Management of Food, Beverages and Public Places in Palangka Raya City, in general, has not been realized properly, this is because (1) The management has not followed the existing regulations (2) and the input has been done but does not give awareness to the manager to comply with it. (3) The IS (Sanitation Inspection) Program has not been optimally carried out.